A mild method for synthesizing carboxylic acids by oxidation of aldoximes using hypervalent iodine reagents. Issue 4 (9th January 2018) - Nakamura, Akira; Kanou, Hodaka; Tanaka, Junki; Imamiya, Akira; Maegawa, Tomohiro; Miki, Yasuyoshi
Abstract : A variety of aldoximes can be efficiently converted into the corresponding carboxylic acids with hypervalent iodine reagent. Abstract : A mild oxidation method for the conversion of aldoximes to carboxylic acids was developed mediated by hypervalent iodine reagents. This method covers a wide range of functionalized aldoximes and proceeds under mild conditions, utilizing PhI(OH)OTs as an oxidant.